Investigating the reasons for using or not using family planning measures by women living in rural area of west Tehran (1994) - Mahvash Roushan Jahromy (Iran University of Medical Sciences, 1998)
A survey was made to study the rational given by women living in rural area of west Tehran for using or not using family planning measures (1994). The purposes of this study were to investigate the reasons for using or not using family planning measures and it's relation to personal characteristics of the subjects. The Samples were grouped in smaller groups: - Those using effective family planning methods - Those using less effective family planning methods at all A total of 427 fertile women randomly were selected from the population of the study. The health clinic's records were used to choose the subjects that fulfilled the conditions for participating in the study. A questionnaire was employed to gather the information, further, the data was analyzed The finding were presented in 43 tables and 10 graphs. Both descriptive and inferal statistics were employed. For further analysis of the findings Xz, Mantel Hanzel and Fisher's exact tests were taken. The overall findings revealed that the rationals for using either method were: belief in planning for desired number of children, availability of contraceptive methods where they lived, satisfaction with the number of children they already had, and economic reasons, respectively. On the other hand the rationals for not using any method were: having children of the same sex, thus desirling for a child of the opposite sex, not having boys specifically, husband not willing and post partum breast feeding. In correlating the personal characteristics of the subjects with the rationals given for either method (effective or less effective) it was assumed that the subjects' age upon marriage, first pregnancy and number of pregnancies were significantly correlated with such rationals as being satisfied with the number of children they had, and being able to limit child bearing as they desired. It was also gathered.ithat age on marriage and first pregnancy, number of pregnancies and level of education were significantly correlated with all the rationals given for not using any method except for post-partum breast feeding. Comparisons of the three groups were made. It was found that a high percentage (65%) of 25-29 years old women were using the effective methods. On the other hand a high percentage (56.6%) of 14-19 year old women were not using either method. Further it was noticed that the less effective methods were practiced by older age groups and those with a history of eight pregnancies or more. In general, of those who did not have a male child, 43.3% were not using any contraceptive method where while only 37% of those who did not have a female child did not use any method. It was also noticed that those who were married to literate men followed family planning means more than those whose husbands were illiterate. Based on the findings suggestions for improving family planning practices were made and further research recommended.